Perempuan di Ruang Virtual yang Maskulin: Mobile Legends sebagai Arena Eksplorasi Konsep Diri dan Negosiasi Gender Gamer Perempuan - Reza Febrianto; Aulia Rahmawati (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study aims to analyze how female gamers construct their self-concept and negotiate gender in the virtual space of Mobile Legends: Bang Bang (MLBB), which is dominated by masculine values. Using a descriptive qualitative approach with in-depth interviews, the study involved seven female informants who are active Mobile Legends players in Surabaya. Findings indicate that female gamers' communication patterns are selective and contextual, shaped by social relationships and perceived safety. Gender-based violence—including stereotypes, skill delegitimization, verbal harassment, and sexual harassment—constitutes a major barrier to female participation. In response, female gamers employ various gender negotiation strategies: concealing identity through neutral usernames, avoiding voice chat, selecting non-feminine heroes, and adapting to toxic environments. Self-concept is formed through two components: cognitive (reflexive awareness of alternative virtual identity) and affective (emotional evaluation of social recognition and self-esteem). The study is grounded in the Proteus Effect theory, Ting-Toomey's Identity Negotiation Theory, and Butler's Gender Performativity Theory